2022
DOI: 10.1111/josi.12523
|View full text |Cite
|
Sign up to set email alerts
|

Parental mental health and child anxiety during the COVID‐19 pandemic in Latin America

Abstract: This study examined parents’ ( N = 10,141, 64% women) reports of their and their childrens’ depression, anxiety, and stress in Brazil, Mexico, Colombia and Argentina. The data come from the COVID‐19 Family Life Study (Ben Brik, 2020) and cohort recruited between April and December 2020. Participants completed online surveys that included the DASS‐21 and the Revised Children's Manifest Anxiety Scale. Our findings indicate that socio‐economically disadvantaged families fared worse in menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 146 publications
(122 reference statements)
2
11
1
1
Order By: Relevance
“…Being in a relationship and caring for someone else have been shown to be protective factors against adversity, whilst unemployment and financial concerns appeared as risk factors for resilience and emotional well-being (Coulombe et al, 2020). The study findings, however, contrast evidence indicating that parental responsibility during the pandemic was associated with emotional distress, in particular among parents of adolescent children (Ben Brik et al, 2022).…”
Section: Discussioncontrasting
confidence: 77%
“…Being in a relationship and caring for someone else have been shown to be protective factors against adversity, whilst unemployment and financial concerns appeared as risk factors for resilience and emotional well-being (Coulombe et al, 2020). The study findings, however, contrast evidence indicating that parental responsibility during the pandemic was associated with emotional distress, in particular among parents of adolescent children (Ben Brik et al, 2022).…”
Section: Discussioncontrasting
confidence: 77%
“…Public health measures aimed at controlling the spread of the disease and reducing infected cases and deaths have also caused negative impacts on people’s health and well-being globally. Evidence suggests that social isolation due to travel restrictions, social distancing, and school closures has produced negative impacts on the mental health of both school children and their parents [ 4 , 5 ]. Compared to children in other age groups, primary school children have been particularly vulnerable during the pandemic, as school closures have led to several changes in their physical and social environments, which consequently affects their mental health.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous literature has shown that primary school children have been affected by public health restriction measures in various ways, including physical activities, sleeping patterns, eating habits, and psychological responses, as well as mental health issues, which include difficulty in concentrating, boredom, irritability, restlessness, nervousness, feelings of loneliness, uneasiness, and worries [ 6 , 7 , 8 , 9 , 10 ]. In addition, depression, anxiety, and stress have been reported among parents who take care of their school-aged children [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence supports a clear inverse relationship between moderate exercise training and the incidence of numerous mental and physical health problems (10,13,21,22,(26)(27)(28)32). So, we mainly recommend moderate-intensity exercise training for healthy and asymptomatic children.…”
Section: Discussionmentioning
confidence: 93%
“…In the study of Ghorbani et al (19), most Iranian adolescents reported symptoms of mild-to-moderate mental health disorders, including depression, anxiety, and stress. Ben Brik et al (32) reported that parental physical activity was associated with better parent and child mental health and anxiety symptoms during the COVID-19 pandemic in Brazil, Mexico, and Colombia. Regarding the effects of decreased physical activity levels on physical health in children and adolescents, most of the observed problems included overweight and obesity and increased BMI (13), negative effects on glycemic control (33), musculoskeletal pain (34), and joint problems (35).…”
Section: Physical Activity and Physical And Mental Health During Coro...mentioning
confidence: 99%